The italian corte di cassazione returns on the issue of recognition of islamic repudiations - Pesce, Francesco (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
With its judgment filed on 7 August 2020, the Italian Corte di cassazione addressed, once again, the issue of the recognition of a foreign repudiation order. As it is well known, the institution of repudiation, which is traditional within Islamic legal systems, has already been the subject of a specific attention in the past in the Italian case-law, which was mainly oriented towards denying the attribution of any effect because of an insurmountable “ontological” conflict between the values underlying this institution in the countries of origin with the principles underlying the so-called international public order of the domestic forum. The contribution aims to examine this position critically, also moving from some isolated signs of a different view, to be found both in the case-law and in the related literature.